2016
DOI: 10.3390/fermentation2040020
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Viability, Physicochemical and Sensory Properties of Probiotic Pineapple Juice

Abstract: (1) Background: Probiotication is an important method in the food industry, and the use of probiotic dairy products has prevented lactose intolerant patients and vegetarians from their consumption. Hence, there is a need to incorporate probiotics in fruit juice without lactose; (2) Method: Probiotic viability, and physicochemical and sensory evaluation of stored probioticated pineapple juice using lactic acid bacteria (LAB) (Pediococcus pentosaceus LaG1, Lactobacillus rhamnosus GG, Pediococcus pentosaceus LBF2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…In another study, the inhibition zone diameters of pineapple juice containing Pediococcus pentosaceus and L. rhamnosus were detected on Klebsiella 10mm, P.aureus 11 mm, Bacillus spp. 13 mm, E.coli 14 mm, Pseudomonas 14 mm, similar to this study 16 . The zone diameters in this study were determined as 14 mm for E. coli and 15 mm for P. aeruginosa.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In another study, the inhibition zone diameters of pineapple juice containing Pediococcus pentosaceus and L. rhamnosus were detected on Klebsiella 10mm, P.aureus 11 mm, Bacillus spp. 13 mm, E.coli 14 mm, Pseudomonas 14 mm, similar to this study 16 . The zone diameters in this study were determined as 14 mm for E. coli and 15 mm for P. aeruginosa.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, commercial products containing probiotics are increasing day by day 25 . In particular, the lack of milk and dairy products as a source of probiotics suitable for consumption by some individuals due to lactose intolerance has led to an increase in alternative probiotic foods and food supplements 16 . Currently, food supplements containing dried probiotics have a fairly large market in this sense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luckow and Delahunty [8] found that for probiotic blackcurrant juice the sensory characteristic was better than the control sample. Some other researchers [28,34] also found similar results in case of mango and pineapple probiotic juice.…”
Section: Discussionsupporting
confidence: 77%
“…The diversity of probiotic food products and the viability of each probiotic in different products at the end of appropriate storage conditions (either freeze or cold storage). Semi hard goat's cheese L. acidophilus B. lactis 10 6 cfu/g 70 days [76] Crescenza [85] Pineapple juice L. casei 10 6 cfu/mL days [86] Pediococcus pentosaceus, Lactobacillus rhamnosus, Pediococcus pentosaceus 10 9 cfu/mL weeks [87] Cashew apple juice powder (spray dried) L. casei NRRL B-442~10 6 cfu/g days [88] Orange juice after Spouted bed drying L. casei~10 6 cfu/g weeks [89] Orange juice powder (spray and freeze dried) L. plantarum 299v 10 6 cfu/g days [90] Orange Lactobacillus GG Not reported [91] Vegetable based African beverages made from maize and milk B. lactis 10 7 cfu/mL days [104] Adapted and modified from [37,51].…”
Section: Dairy Vs Non-dairy Food Matricesmentioning
confidence: 99%